Beyond The Algorithm: The Mediating Role of Perceived Value in Driving Customer Loyalty - Julina Julina; Nurlasera Nurlasera; Desrir Miftah; Qonitah Rifda Zahirah (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
In the era of rapid digital commerce, understanding the factors that drive customer loyalty in online shopping is crucial for retailers seeking to maintain a competitive advantage. This study examines the impact of Product Recommendation Relevance, Content and Promotion Personalization, and Adaptive Navigation Ease on Perceived Value and Customer Loyalty, considering both direct and indirect effects through perceived value. Data from 162 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Product Recommendation Relevance significantly influences Perceived Value and has a significant indirect effect on loyalty, though its direct effect on loyalty is not significant. In contrast, Content and Promotion Personalization does not significantly affect either perceived value or loyalty, directly or indirectly. Adaptive Navigation Ease has a significant positive effect on both Perceived Value and Customer Loyalty, and also exhibits a significant indirect effect on loyalty through perceived value. Moreover, Perceived Value plays a strong mediating role, significantly influencing customer loyalty. These findings highlight that improving navigation ease and delivering relevant product recommendations are key strategies to enhance perceived value and foster customer loyalty. From a managerial perspective, online retailers should prioritize optimizing website or app navigation and curating product recommendations, while personalization efforts should be carefully aligned with consumer preferences to effectively impact loyalty.